2019
DOI: 10.4028/www.scientific.net/msf.963.553
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Non-Ideal Ohmic Contacts on the Performance of High-Voltage SiC MPS Diodes

Abstract: The wide band gap of SiC semiconductor devices constitutes a serious challenge to build good Ohmic contacts on the surface of the p-type material. This is reflected in the numerical analysis of ”realistic” devices, where we have to cope with serious problems, such as a shifting threshold voltage, reduced forward conductivity, and no noticeable conductivity modulation by minority carrier injection from p+-emitters, in matching measured data with simulation results, as a consequence of the significant impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…We found that the Schottky barrier of JBS-diode II is almost 1 eV higher than that of JBSdiode I. The increase of this potential barrier with decreasing ratio Ws/WPin can be attributed to the depletion layers along the p + n --junctions, which have to recede before electrons can flow from the Schottky contact to the drift zone [4]. Fig.…”
Section: Forward Conduction At Low Electric Current Densitymentioning
confidence: 77%
“…We found that the Schottky barrier of JBS-diode II is almost 1 eV higher than that of JBSdiode I. The increase of this potential barrier with decreasing ratio Ws/WPin can be attributed to the depletion layers along the p + n --junctions, which have to recede before electrons can flow from the Schottky contact to the drift zone [4]. Fig.…”
Section: Forward Conduction At Low Electric Current Densitymentioning
confidence: 77%
“…Exploiting the potential of silicon carbide electrophysical parameters requires from ohmic contacts to SiC-based devices demonstration of low resistivity, stable electrical conductivity, high oxidation resistance and reliability, especially when operating at elevated temperatures. Insufficient electrical conductivity of ohmic contacts due to degradation of metal/SiC interface or relatively high specific contact resistance ρc (>10 -3 Ωcm 2 ) may result in an unacceptably high voltage drop at the contact, and thereby deterioration or even making impossible operation of silicon carbide devices [3,4].…”
Section: Introductionmentioning
confidence: 99%